1997
DOI: 10.1159/000217442
|View full text |Cite
|
Sign up to set email alerts
|

Activated-Protein-C Resistance in Cancer Patients

Abstract: Background: Resistance to activated protein C (aPC) is usually linked to factor V Leiden, but may occur in other disorders associated with hypercoagulability. In this study, we investigated the frequency of resistance to aPC in patients with advanced cancer and examined the relationship of aPC resistance to other markers of coagulation activation. Methods: Patients (n = 39) had an established diagnosis of advanced cancer; controls (n = 20) were healthy persons. aPC resistance was measured as the ratio of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 16 publications
4
43
3
Order By: Relevance
“…41,42,49 However, in malignant conditions other than ET and PV, the appearance of APC-resistant phenotype has been determined by increased levels of plasma FV and factor VIII (FVIII), instead of decreased PS levels. 40,41,50,51 In conclusion, we have shown that plasma from ET and especially PV patients is APC-resistant, which may account for the increased thrombotic risk associated with these disorders. This study provides a new insight in the pathogenesis of the thrombophilic state in patients with ET and PV by linking together the appearance of acquired APC resistance (a condition that is associated with an increased thrombotic risk), the occurrence of reduced levels of specific coagulation factors and neutrophil activation, and JAK2 V617F mutational status.…”
Section: Org Frommentioning
confidence: 82%
“…41,42,49 However, in malignant conditions other than ET and PV, the appearance of APC-resistant phenotype has been determined by increased levels of plasma FV and factor VIII (FVIII), instead of decreased PS levels. 40,41,50,51 In conclusion, we have shown that plasma from ET and especially PV patients is APC-resistant, which may account for the increased thrombotic risk associated with these disorders. This study provides a new insight in the pathogenesis of the thrombophilic state in patients with ET and PV by linking together the appearance of acquired APC resistance (a condition that is associated with an increased thrombotic risk), the occurrence of reduced levels of specific coagulation factors and neutrophil activation, and JAK2 V617F mutational status.…”
Section: Org Frommentioning
confidence: 82%
“…Levels of factor VIII and D-dimer are reported to be considerably high in cancer patients compared to healthy control subjects. 7 Procoagulant activity has been shown to be associated with stage of the disease. 8 Possible causes of increased procoagulants seem to be endothelial cell damage, endothelial synthesis (accelerated with the induction of tumour during angiogenesis), endothelial proliferation or an acute phase reaction due to vascular abnormalities, in addition to activation of the coagulation system as a result of increased tissue factor.…”
Section: Discussionmentioning
confidence: 99%
“…19 Previous studies have also found an increased prevalence of acquired APC resistance in patients with cancer. [46][47][48] It is licit to assume that two sources of APC resistance (i.e. acquired and inherited) in cancer patients would greatly increase the risk of a VTE, similarly to the synergistic effect of oral contraceptive use in individuals with FVL, as both result in a poor response to APC.…”
Section: Discussionmentioning
confidence: 99%